Social marketing for a farmer's market in an underserved community: A needs assessment - Meg Skizim; Melinda Sothern; Ondrej Blaha; Tung Sung Tseng; Lauren Griffiths; Jonathan Joseph; Henry Nuss (SAGE Publishing, 2018)
The aim of the present paper is to assess local residents' awareness of utilizing Supplemental Nutrition Assistance Program (SNAP) benefits to purchase fresh produce at local farmers' markets, and to determine internet use and media preferences of study participants prior to implementation of a social marketing campaign. A needs assessment was conducted to collect baseline data in an underserved neighbourhood in New Orleans (LA, USA). The study was carried out August 2014-May 2015. The assessment revealed that 73% of the respondents were unaware that the SNAP benefits could be used to purchase food in farmers' markets; 63% of low-income participants never attended a farmers' market compared to 27% of mid/high-income. Over 50% of the low-income respondents have access to the internet at least once per day. The results show the potential of raising awareness among a wide range of members in the community. This needs assessment will serve as the foundation for a social marketing intervention, which will be disseminated city-wide.